ANALISIS PERUBAHAN KARAKTERISTIK CURAH HUJAN DAN DAMPAKNYA TERHADAP MUSIM TANAM PADI DI KECAMATAN KOTO TANGAH KOTA PADANG - Tjandra, M. Agita; Yanti, Delvi; Zawiyah (Jurnal Teknologi Pertanian Andalas, 2025)
Climate change affects rainfall patterns, causing shifts in the onset of seasons that impact water resource availability, thereby disrupting crop growth, yields and agricultural production. Rainfall variability, both spatially and temporally, can lead to changes in the planting and harvesting seasons of crops, which in turn affect the food security of a region. The objectives of this study were to identify rainfall characteristics in Koto Tangah District, identify the rice planting season in Koto Tangah District, and analyze the effect of changes in rainfall characteristics on the rice planting season in Koto Tangah District. The research employs a combination of quantitative and qualitative methods, presented in a descriptive and explanatory manner. The analysis to observe changes in rainfall characteristics was conducted over three periods: quarterly, semi-annualiy, and annually. The rainfall characteristics analyzed were minimun, maximum, average and total rainfall. After analyzing rainfall characteristics, changes in rainfall characteristics were integrated with the rice planting season in Koto Tangah District, Padang City. Based on the analysis results, it was conducted that there were changes in rainfall characteristics in Koto Tangah District, Padang City, however farmers did not use rainfall as the primary reference for determining the rice planting time. Koto Tangah District already has a good technical irrigation network, enabling it to provide water for rice fields throughout the year. In addition to being supported by good technical irrigation, Koto Tangah District has relatively high rainfall every year. Therefore, changes in rainfall characteristics do not affect the rice planting season in Koto Tangah District.